Discourses of positionality and the challenges of democratization in the global south: The case of Nepal and Cameroon - Thorsen, Jacob; Ngomba, Teke J (MedieKultur: Journal of media and communication research, 2012)
In this article, we argue that to conceptually and empirically grasp the dynamics and challenges of processes of civic participation, i.e., the deliberation and empowerment of disenfranchised and marginalized populations in the Global South, communication for social change scholars need to pay more attention to three issues: the quality of citizens’ self-perceptions in relation to their local milieu, inter-citizen perceptions and relations at the local level and lastly, the attendant consequences of these on citizens’ sense of efficacy. To grasp and comprehend the interplay of these three issues, we propose the adoption of Floya Anthias’ concept of narratives of location and positionality and demonstrate the heuristic vitality of this notion through a discussion of some local discourses of positionality in Nepal and Cameroon.